(untitled) (CIPEEX, 2025)
This study examines the Jury Court’s competence to determine whether a homicide was motivated by jealousy and whether such feeling, in the concrete case, qualifies the offence; it is a jurisprudential analysis illustrated with a contrasting evidentiary hypothesis. It aims to delineate the judge’s role at the indictment (pronúncia) stage and the operation of the in dubio pro societate principle when there is controversy over justifications such as self-defence. Methodologically, it reviews precedents that safeguard the jury’s sovereignty and allow the exclusion of qualifying circumstances only when they are manifestly unfounded, coupled with a scenario of divergent witness statements to demonstrate the need to submit the theses to the Jury Panel. The results indicate that the bench judge may not replace the jurors’ assessment regarding qualifying circumstances or justifications when reasonable doubt persists and must commit the defendant to trial so that the versions are assessed by the jury; they also show that jealousy, by itself, does not automatically qualify homicide and requires contextual factual scrutiny. It concludes that assessing motive (jealousy) and justifications lies within the Jury Court’s remit, and that prior judicial intervention is limited to rejecting qualifiers only when their impropriety is evident, thereby preserving the jury’s constitutional competence.